(untitled) (International journal of artificial intelligence, 2025)
Storytelling brings the dry rules in the textbook to life and transforms grammar into meaning through thoughts, events, and characters. The main idea of teaching English grammar through storytelling is that students do not memorize the rule separately, but perceive and remember it in context; language forms are stored in long-term memory and become automatic when connected with the purpose of communication. The story shows students "why" and "where" the language is used - deepening their understanding of grammar. This article discusses the benefits of using storytelling in teaching English grammar.